Avaliação da qualidade de salmouras empregadas na salga de queijos de laticínios inscritos no Serviço de Inspeção do Paraná (SIP) na microrregião de Francisco Beltrão - PR - Bortolon, Evelin (2012)
Salting is one of the most important steps in the cheese manufacturing, and can be used in various ways, for example, in milk, in mass, brine and dried. By brine salting aims mainly to salt with higher quality covering all areas of the product, and is the main mode and more traditionally used in Brazil. Thus, the quality of brine must be observed. The aim of this study was to evaluate the quality of brines used in salting of cheese in dairy enrolled in Paraná Inspection Service - SIP, Francis Beltran in micro-PR. Analyses physicochemical acidity, pH and salt concentration. Microbiological analyzes were performed mesophilic count, yeasts and molds, Most Probable Number (MPN) of coliforms at 35º C and 45º C and also the presence of Salmonella sp. It can be seen from the results, that the pickles evaluated showed good physicochemical quality, but we observed failures when it comes to microbiological standards for mesophilic microorganisms, yeasts and molds. Thus, it is evident that there must be a more effective quality control Pickles, since it is directly related to the quality of the cheese.